Creation of Faceted Polyhedral Microgels from Compressed Emulsions. Issue 31 (26th June 2017) - Fan, Jing; Kim, Shin‐Hyun; Chen, Zi; Zhou, Shaobing; Amstad, Esther; Lin, Tina; Weitz, David A.
Abstract : Compressed monodisperse emulsions in confined space exhibit highly ordered structures. The influence of the volume fraction and the confinement geometry on the organized structures is investigated and the mechanism by which structural transition occurs is studied. Based on the understanding of ordering behavior of compressed emulsions, a simple and high‐throughput method to fabricate monodisperse polyhedral microgels using the emulsions as the template is developed. By controlling the geometry of the confined spaces, a variety of shapes such as hexagonal prism, Fejes Toth honeycomb prism, truncated octahedron, pyritohedron, and truncated hexagonal trapezohedron are implemented. Moreover, the edge sharpness of each shape is controllable by adjusting the drop volume fraction. This design principle can be readily extended to other shapes and materials, and therefore provides a useful means to create polyhedral microparticles for both fundamental study and practical applications. Abstract : Inspired by dispersion systems of two immiscible fluids, a simple and high‐throughput method to create microgels with a variety of polyhedral shapes from monodisperse compressed emulsions is developed. To better understand the ordering behavior of compressed emulsions, the influence of the volume fraction of the drops and the geometry of the confinement on the organized structures is investigated and the mechanism by which structural transition occurs is studied.